The Wigan Dandy: Promenading the dance hall via Detroit and Paris. Issue 1 (1st April 2013) - Nicholson, Sue
In this short article, I intend to consider the transnationalism inherent within the Northern Soul movement of the 1970s. By contextualizing the sociocultural climate from which this group emerged, the article will argue that by challenging masculinity through performance and dress practices, Northern Soul devotees borrowed not merely from the disaffected black ghettos of Detroit, but from the streets of nineteenth-century Paris.